Comparing the effect of blue-light lenses and built-in blue light Filtering software in electronic devices on accommodation accuracy during digital reading in the dark - Rosli, Saiful Azlan; Che Azemin, Mohd Zulfaezal; Chen, Ai-Hong (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2022)
Introduction: Blue light from electronics are linked to several visual problems including blurry vision, eyestrain, dry eye, macular degeneration, and cataracts. Lenses and software that are designed to block out blue light have been recommended for digital reading, but their visual impact remains debatable. This study aims to investigate the effect of blue-blocking ophthalmic lens (BBOL) and built-in blue light filtering software (BIBLFS) on digital reading in the dark on accommodation accuracy. Methods: This cross-sectional study design was approved by the UiTM ethics committee. Fifteen young adults were recruited using convenience sampling. The accommodation response of 1-min direct digital reading (DDR) from an iPad at 40 cm in a dark room was measured using Grand Seiko WAM5500. The digital reading in the dark was repeated with BBOL and with BIBLFS. There was a 5-min dark adaptation in between each testing condition. The spectral transmittance was analysed using Retinal Index (RI) and Circadian Index (CI).Results: The comparison of accommodation response in three testing conditions (DDR – BBOL – BIBLFS) revealed no significant difference (F = 1.735, p > 0.05). However, our RI and CI analysis revealed that BBOL and BIBLFS displayed different protective effects against spectral emission from the electronic display compared to the standard illuminate test. Conclusion: The effects of BBOL and BIBLFS on accommodation response was negligible in short-term digital reading in the dark. However, the long-term accumulative effects on the accommodation system after prolonged usage requires further investigation